Becoming a Different Teacher: Exploring English Teachers’ Professional Identity Transformation after an In-Service Certification Program - Desy Ireny Leimena; Karol Anaktototy; Inggrit Tanasale (ITScience (Information Technology and Science), 2026)
This study explores how English teachers experience a transformation in professional identity after completing an in-service certification program. Grounded in transformative learning theory, particularly Mezirow’s concept of perspective transformation, this research adopts a phenomenological approach to examine teachers’ lived experiences. Data were collected through in-depth interviews with three English teachers who had completed the certification program. The findings reveal that teachers underwent significant shifts in their professional identity, beginning with the recognition of limitations in their prior teaching practices. These experiences prompted critical reflection, leading to the adoption of more student-centred and reflective pedagogical approaches. The study also shows that teachers reconstructed their professional identity, viewing themselves as more competent, confident, and responsible educators. However, this transformation was accompanied by challenges, including limited resources and la ack of institutional support, which created tensions in implementing new practices. This study contributes to the literature by highlighting the role of transformative learning in shaping teacher identity and underscores the need for contextualised support in professional development programs.